2018
DOI: 10.1038/s41598-018-22530-3
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas released from the deep permafrost in the northern Qinghai-Tibetan Plateau

Abstract: Deep carbon pool in permafrost regions is an important component of the global terrestrial carbon cycle. However, the greenhouse gas production from deep permafrost soils is not well understood. Here, using soils collected from 5-m deep permafrost cores from meadow and wet meadow on the northern Qinghai-Tibetan Plateau (QTP), we investigated the effects of temperature on CO2 and N2O production under aerobic incubations and CH4 production under anaerobic incubations. After a 35-day incubation, the CO2, N2O and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 51 publications
0
15
1
1
Order By: Relevance
“…荒漠草原区土 解 [49] . 对深达5 m的多年冻土样品进行有氧和厌氧培 养, 发现各深度样品的N 2 O、CH 4 和CO 2 释放速率相 似 [50] . 高原上与铁吸附的碳约占总有机碳比例的20%, 是惰性碳库的一部分 [51] .…”
Section: 青藏高原年冻土与碳循环unclassified
“…荒漠草原区土 解 [49] . 对深达5 m的多年冻土样品进行有氧和厌氧培 养, 发现各深度样品的N 2 O、CH 4 和CO 2 释放速率相 似 [50] . 高原上与铁吸附的碳约占总有机碳比例的20%, 是惰性碳库的一部分 [51] .…”
Section: 青藏高原年冻土与碳循环unclassified
“…Thus, the timing of the thaw date advances and the number of thawing days increases, as shown in this study, which prolongs the growing season. As part of this process, an increase in active layer depth likely leads to an increase in organic matter decomposition and hence nutrient availability, which then also leads to an increase in greening (Fisher et al, ; Mu et al, ; Walz et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some soil culture experiments showed that the main factor that increased carbon emission in frozen soil was temperature rise, and the relationship between carbon emission and soil depth was not obvious. Therefore, future warming would lead to an increase in carbon emissions from the entire soil layer [80]. On the contrary, the same infrared heating experiment on frozen soil predicted that the plateau frozen soil would become a carbon sink in the future because the gross ecosystem production (GEP) brought by warming was higher than that of the ecosystem respiration (ER) [70].…”
Section: Whether To Consider Frozen Soil Experimental Scenario Main Imentioning
confidence: 99%